2011
DOI: 10.1007/s00107-011-0540-4
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss der thermischen Modifizierung von Holz auf das Wasserrückhaltevermögen (WRV-Wert)

Abstract: Thermal modification of wood (ash, beech, spruce) leads to a remarkable decrease in the Water Retention Value (WRV). In case of beech wood the WRV-value decreased after immersion in water for 72 h from 55.5% to 40.5% (about 27%) and in case of spruce wood from 49.3% to 34.5% (about 30%). The decrease in the WRV of ash wood was relatively low (about 19%). The WRV-method seems to be useful to follow up the process of thermal modification of wood. Ziel der UntersuchungenDie Modifizierung von Holz durch thermische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The existence of lignin decreases the water‐holding properties, while hemicellulose increases the WRV of fibers. The beating of fibers during mechanical treatment creates modifies fibers structures by breaking intra and intermolecular bonds, which also improves water absorption properties [17] . Cellulose has amorphous and crystalline regions.…”
Section: Resultsmentioning
confidence: 99%
“…The existence of lignin decreases the water‐holding properties, while hemicellulose increases the WRV of fibers. The beating of fibers during mechanical treatment creates modifies fibers structures by breaking intra and intermolecular bonds, which also improves water absorption properties [17] . Cellulose has amorphous and crystalline regions.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in particles thermally modified at 180 °C for 1.5 hours, Weigl et al (2013) reported a decrease of 28.0 % and 46.0 % of the water retention capacity, which is related to the reduction of polarity. Coincidentally, Roffael and Kraft (2012) indicate that the thermal modification of the wood leads to a marked decrease of the water retention capacity. After subjecting particles to heat treatment, these authors reported a decrease in water retention values (after 72 hours in water) of 27.0 % for Fagus sylvatica, 19.4 % for Fraxinus excelsior and 30.0 % for Picea abies.…”
Section: Water Retention Capacity 32 Kapacitet Zadržavanja Vodementioning
confidence: 94%
“…The wettability of heat treated wood particles decreases in treated fibers (Poblete, 1983;Crespo et al, 2013) as well as water retention capacity (Roffael and Kraft, 2012;Weigl et al, 2013). The higher the temperature and the exposure time of heat treatment, the lower the amount of water absorbed by the wood (Poblete, 1983; Kartal et al, 2007.…”
Section: Uvodmentioning
confidence: 99%
“…However, it is not effective against thermites [19,20]. Thermal modification reduces the equilibrium moisture content (EMC) of ash [3,21,22] and decreases its water retention value [23], enhancing its dimensional stability [22,24,25]. It also alters the natural colour of wood, making it darker with the increasing severity of the treatment [3,21,26] as well as improves its resistance to weathering factors as regards colour stability, surface quality, and the reduction rate for strength properties [21,27,28].…”
Section: Introductionmentioning
confidence: 99%